Cytochrome P450, Arylhydrocarbon hydroxylase and xanthine oxidase activity during sublethal malathion exposure in freshwater catfish Heteropneustes fossilis - Borthakur, Mridul Kumar (Journal of the Inland Fisheries Society of India, 2016)
Bio-accumulation and environmental persistence of organochlorine pesticides have led to progressive increase in the use of organophosphorus (OP) pesticides like malathion. Effect of OP pesticide, malathion on three hepatic mixed function oxygenase (MFO) enzymes – cytochrome P450, arylhydrocarbon hydroxylase (AHH) and xanthine oxidase (XOD) of Heteropneustes fossilis were studied in laboratory condition. Fishes were exposed to malathion in two sublethal concentrations. Activity of three MFO enzymes were estimated in experimental and control groups from the day of treatment upto one month. Cytochrome P450 and xanthine oxidase (XOD) activities were consistently andsignificantly higher in malathion exposed group at different time exposures compared to control group. Arylhydrocarbon hydroxylase activity in response to malathion exposure was minimal relative to the other two enzymes. It has beenfound that malathion at sub-lethal concentration can act as inducer of hepatic MFO enzymes in Heteropneustes fossilis.